THE IMPORTANCE OF FOREST AND LANDSCAPE RESOURCE FOR COMMUNITY AROUND GUNUNG LUMUT PROTECTED FOREST, EAST KALIMANTAN - Murniati Murniati; Michael Padmanaba; Imam Basuki (Indonesian Journal of Forestry Research, 2009)
The forest of Gunung  Lumut  in Pasir District,  East Kalimantan was designated  for a protection  forest in 1983. It is surrounded  by 15 villages  and one settlement  lies inside it. Communities in those villages are dependent upon the landscape and forest resources mainly for non timber forest products. This study was focused on the perception of the communities on the importance of the landscape and forests. The study was conducted in two settlements, located  in and outside  (near)  the protection  forest,  namely  Rantau  Layung  Village  and Mului  Sub-Village.  Data collection  was undertaken through  general field observations, key- informant personal  interviews and focus group  discussions.  In Rantau  Layung, the most important land  type  was rice  field, whereas  in Mului  was forest.  There  were  13 and 14 use categories  of landscape  resources  in Rantau  Layung  and Mului,  respectively, such as food, medicine,  constructions and source of income.  People in Rantau  Layung  and Mului ranked  plants  to be more  important than  animals.  People  also considered  products  from wild  resources  to be more  important than  those from cultivated  and purchased  sources. Communities living  in both  settlements  considered  the future  uses of forests to be the most important as compared to those of the present and past. They  suggested that sungkai (Peronema canescens) and telien (Eusideroxylon zwageri) to be the most important plants while payau  (Cervus unicolor) and telaus (Muntiacus muntjak) to be the most important animals. People used the wildlife mainly for food and source of income. They also identified important and potential  resources for economic  development in the area, i.e. ecotourism  and hydro- power for electric  generator.